1999
DOI: 10.1002/(sici)1097-0134(19990301)34:4<520::aid-prot11>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and functional variability supported by the BPTI fold: Solution structure of the Ca2+ channel blocker calcicludine

Abstract: Calcicludine, a 60-amino acid protein isolated from the green mamba venom, has been recently identified as blocking a large set (i.e., L-, N- and P-type) of Ca2+ channels. The three-dimensional structure of calcicludine has been determined by NMR and molecular modeling using a data set of 723 unambiguous and 265 ambiguous distance restraints, as 33 phi and 13 chi1 dihedral angle restraints. Analysis of the 15 final structures (backbone root-mean-square deviation = 0.6 A) shows that calcicludine adopts the Kuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Sequence of BF9 aligned with those of seven BPTI-like superfamily proteins for which three-dimensional solution structures have been determined. These are BPTI (3), C5 (6, 37), the S. helianthus proteinase inhibitor (ShPI) (7), dendrotoxin I (DTI) (12), DTK (11), calcicludine (CALC) (13), and TAP (15). The three disulfide bridges are shown by brackets.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence of BF9 aligned with those of seven BPTI-like superfamily proteins for which three-dimensional solution structures have been determined. These are BPTI (3), C5 (6, 37), the S. helianthus proteinase inhibitor (ShPI) (7), dendrotoxin I (DTI) (12), DTK (11), calcicludine (CALC) (13), and TAP (15). The three disulfide bridges are shown by brackets.…”
Section: Methodsmentioning
confidence: 99%
“…This project name will be used to generate the file names at the different stages of the protocol. We will use the 1bf 0 structure [55] as an example, with the corresponding NMR restraints available for this entry from the BioMagResBank (BMRB) [56]. The easiest way of obtaining the restraints in a format ready to be used in this protocol is to go to the BMRB from the PDB entry, select 4-filtered-FRED in the stage window, select the distance restraints in XPLOR/CNS format by clicking on it, and then click on "170823" in mrblock id and copy and paste these restraints in a text file called unambig.tbl (see Note 1).…”
Section: Nmr Structure Calculation and Refinementmentioning
confidence: 99%
“…Therefore, we compared the results of our localization studies with those of Imredy et al who characterized the binding δ-dendrotoxin to the inward rectifying (K ir 1.1) and voltage-gated (K V 1.1) K+ channels (24,25). Like calcicludine, δ-dendrotoxin is a member of the BPTI/Kunitz-like toxin family (15,18). Neutralization of Glu-123 of K ir 1.1 results in a mutant channel with an IC 50 for half-maximal block by δ-dendrotoxin that is more than 250-fold larger than wild-type (24), and substitution of alanine for Asp-431 results in a 160-fold increase in the IC 50 for half maximal block of K V 1.1 channels by δ-dendrotoxin (25).…”
Section: Calcicludine and δ-Dendrotoxin Share Similar Pharmacologicalmentioning
confidence: 99%
“…1A). Because of its folding pattern, calcicludine is classified as a bovine pancreatic trypsin inhibitor (BPTI)/Kunitz-like toxin (14)(15)(16)(17) and is structurally homologous to the K + channel selective dendrotoxins (18). Schweitz et al reported that N-and P/Q-type currents are effectively blocked by calcicludine (16).…”
mentioning
confidence: 99%